Raya Dunayevskaya's Intersectional Marxism Race, Class, Gender, and the Dialectics of Liberation - Anderson, Kevin B.; Durkin, Kieran; Brown, Heather A. (Marx, Engels, and Marxisms, 2021)
XXI, 350 p. 1 illus.